Development of Conservation E-Books Based on Local Potential to Improve Eco-literacy of Junior High School Students - Erfariyah, Ai; Jaenudin, Dadang; Permana, Irvan (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This research aimed to develop a conservation e-book based on local potential to improve the eco-literacy of junior high school students. The development of the e-book is based on the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) which was conducted on 27 seventh-grade students using a one-group pretest-posttest design. The development instruments were in the form of validation forms, eco-literacy questions, and questionnaires as well as student response surveys to conservation e-books. Analysis was conducted on the results of validation of e-book feasibility, increase in gain value, and hypothesis testing. The results of data analysis showed that the developed conservation e-book was declared valid with a percentage of 93.20% from material experts and 93.39% from media experts. In addition, after using local potential-based conservation e-books, there is an increase in eco-literacy with an average N-Gain value of 0.65 (knowledge competency) and 0.46 (attitude competency, skills, and human relations with nature) respectively, including in the moderate category. The test of the effectiveness of eco-literacy knowledge competence using the Paired-T Test shows a sig. value of 0.000, as well as the competence of attitudes, skills, and human relations with a nature of 0.000. Students' response to the e-book was very good as indicated by a percentage value of 94%. Thus, conservation e-books based on local potential can improve students' eco-literacy and are effectively used in the science learning process.